2010
DOI: 10.1080/10934529.2010.513296
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic sources and environmentally relevant concentrations of heavy metals in surface water of a mining district in Ghana: a multivariate statistical approach

Abstract: The levels of heavy metals in surface water and their potential origin (natural and anthropogenic) were respectively determined and analysed for the Obuasi mining area in Ghana. Using Hawth's tool an extension in ArcGIS 9.2 software, a total of 48 water sample points in Obuasi and its environs were randomly selected for study. The magnitude of As, Cu, Mn, Fe, Pb, Hg, Zn and Cd in surface water from the sampling sites were measured by flame Atomic Absorption Spectrophotometry (AAS). Water quality parameters inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 24 publications
0
40
0
1
Order By: Relevance
“…The guideline value for cadmium is given as 0.003 mg/L in Science Publications AJES drinking water by both the World Health Organization (WHO, 2004) and the Nigerian standard for drinking water quality (SON, 2007). Previous studies show maximum levels in groundwater to be 0.003 mg/L (Kortatsi, 2004;Armah et al, 2010) and 0.06 mg/L (Oluwasanya and Martins, 2006). Maximum levels in surface water were less than 0.05 mg/L (Kuma and Younger, 2004;Yem et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The guideline value for cadmium is given as 0.003 mg/L in Science Publications AJES drinking water by both the World Health Organization (WHO, 2004) and the Nigerian standard for drinking water quality (SON, 2007). Previous studies show maximum levels in groundwater to be 0.003 mg/L (Kortatsi, 2004;Armah et al, 2010) and 0.06 mg/L (Oluwasanya and Martins, 2006). Maximum levels in surface water were less than 0.05 mg/L (Kuma and Younger, 2004;Yem et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic and acute poisoning by arsenic due to exposure to elevated concentrations is a common occurrence. High arsenic concentration in TSF-DW could be attributed to leaching of the element by cyanide from arsenopyrite ore mined by ARL (Armah et al, 2010). Welch, Lico, & Hughes (1988) reported that arsenic is an important auxiliary contaminant in mine waters, particularly where the ore bodies contain arsenopyrite as is the case at ARL.…”
Section: Arsenic Cadmium and Mercurymentioning
confidence: 99%
“…Contents of TSFs could therefore be highly contaminated and are therefore not discharged directly into the environment in conformity with international best practice for mining industries. It is therefore imperative to properly manage tailings as they constitute a major source of release of many trace elements and other contaminants into the environment (Armah et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Mn and Pb are also associated with Zn (r=0.99 and 0.82) indoors, which may due to the emissions of paints, varnishes usage, in leather industry, along with polluted road dust [33]. The high correlations between heavy metals in air may reflect the fact that these heavy metals had similar pollution levels and similar pollution sources such as shaving, buffing and anthropogenic activities [34,35].…”
Section: F Correlation Matrixmentioning
confidence: 95%